BENIGN AND MALIGNANT HYPERTENSION AFTER ADRENAL ENUCLEATION IN THE RAT : RELATIONSHIP TO SALT INTAKE, RESPONSE TO HYDROCHLOROTHIAZIDE, AND SIMILARITY TO ESSENTIAL HYPERTENSION - Hall, C. E. (The Rockefeller University Press, 1967)
Adrenal-enucleated, mononephrectomized rats given a high salt diet rapidly develop malignant hypertension, characterized by the presence of necrotizing vascular lesions in a number of organs and tissues. If a normal salt intake is provided, or if hydrochlorothiazide is given together with a high salt diet, there is, instead, the delayed onset of benign hypertension which either stabilizes or increases in intensity extremely slowly; Such animals display few, if any, pathologic vascular changes other than occasional focal glomerular hyalinization, show insignificant cardiac enlargement, and do not exhibit alterations in the serum sodium or potassium. Occasional animals behave atypically and develop malignant hypertension despite normal salt consumption, demonstrating that in susceptible rats excess salt is not essential to this disorder. Hydrochlorothiazide given to rats that imbibed distilled water postoperatively prevented hypertension entirely for 97 days, when one of eight rats developed mild hypertension and some others reached what is regarded as a prehypertensive range. It is concluded that adrenal regeneration provides a physiological milieu favorable to the development of benign hypertension, which is not, as a rule, manifest until regeneration is complete. Salt excess converts the response into one in which malignant hypertension begins during regeneration and worsens rapidly thereafter until death. The course and findings are compared with those of the benign and malignant phases of clinical essential hypertension, and the implications of the similarities are discussed.